Effect of Development Aid on Productive Capacities - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2021)
The international policy discourse, for example by the World Trade Organization and the United Nations, has emphasized the critical role of productive capacities in promoting sustainable development and building economic resilience in developing countries. This paper has examined whether development aid contributes to enhancing productive capacities in recipient countries. To that effect, it considers two main components of the total official development assistance (ODA), including Aid for Trade (AfT) and NonAfT, the latter being the part of total ODA allocated to other sectors than the trade-related sectors. The analysis relies on the index of the overall productive capacities developed recently by the UNCTAD, and covers 111 countries over the period 2002-2018. The findings indicate that development aid, including its two main components contribute to fostering productive capacities in recipient countries, with AfT flows exerting a higher positive effect on productive capacities than NonAfT flows. Moreover, in Least developed countries (LDCs), the positive effect of ODA on productive capacities reflects the key role of both AfT flows and NonAfT flows in contributing to the development of productive capacities. In contrast, in NonLDCs (other countries in the full sample than LDCs), only AfT flows matter positively for the strengthening of productive capacities, as NonAfT flows do not appear to exert a significant effect on productive capacities. These outcomes highlight the criticality of development aid for enhancing productive capacities in developing countries, in particular in LDCs.
Keywords: D24; O1; F35; 330; Development aid; Productive Capacities